2021
DOI: 10.1590/1518.8345.4769.3448
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic and nurses’ attitudes toward death

Abstract: Objective: to analyze nurses’ attitudes toward death in a hospital context after the critical period of the COVID-19 pandemic in Portugal. Method: this quantitative, descriptive, exploratory study was conducted in a university hospital and addressed 995 nurses. Revised Death Attitude Profile (DAP-R) was used to collect data, which were analyzed using analytical and inferential statistics. Results: the nurses most frequently agreed with the statements concerning the Neutral/Neutrality Acceptance and Fear. Age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 19 publications
2
21
0
1
Order By: Relevance
“…Thai people regularly listen to the most recent updates on the number of cases and deaths from COVID-19. Furthermore, a prior study on the COVID-19 pandemic and attitudes toward death have showed that the participants featured attitudes of fear and avoidance [ 42 ]. This may alter the attitude of participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thai people regularly listen to the most recent updates on the number of cases and deaths from COVID-19. Furthermore, a prior study on the COVID-19 pandemic and attitudes toward death have showed that the participants featured attitudes of fear and avoidance [ 42 ]. This may alter the attitude of participants in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to nursing professional practice environments, the investment made in the institution during the first two critical periods of the pandemic, such as the increased availability of material resources, the hiring of more nurses, the mobilization of nurses from services with decreased activity to those that ensured care for COVID‐19 patients, the strict separation of COVID and non‐COVID areas and the frequent assessment of the adopted strategies (Almeida, 2020 ; Cardoso et al, 2021 ), had a positive impact on the Structure and Outcome components. However, the mean percentages confirm that, similarly to the pre‐pandemic context, these components remained moderately favourable to the quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various implemented measures, we highlight the acquisition of clinical and non‐clinical material and the early definition of independent circuits for patients with COVID‐19. In addition, some services were remodelled, and professionals were hired to satisfy more adequate ratios, as well as reinforced training and constant dissemination of guidelines issued by national and international entities (Almeida, 2020 ; Cardoso et al, 2021 ; Ventura‐Silva et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudo sobre as atitudes de enfermeiros portugueses frente à morte no período crítico pandêmico, em ambiente hospitalar e principalmente na área de atendimento da COVID-19, aponta média superior em relação às atitudes de medo (28,9%) e de evitamento (18,4%), ou seja, medo da morte e evitar pensar sobre ela, com o objetivo de minimizar ansiedade. Salienta também que a atitude de medo perante a morte em pessoas casadas, em união estável e/ou que vivem com companheiros é mais significativa (Cardoso et al, 2021), o que corrobora achados do presente estudo, em que o medo de morrer foi expresso majoritariamente por profissionais casadas. Portanto, é fundamental que nos processos formativos e de capacitação, estudantes e profissionais de enfermagem recebam conteúdos e discorram sobre como lidar e enfrentar situações de morte no contexto do cuidado.…”
Section: Discussionunclassified